Religion of Ladies Companion: The Woman ‘Habitus’ in Karaoke Place at Mojokerto City - Taufiqurrohim; Aluviera Mardiansyah Putri (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Ladies Companion (LC) is a profession that has a very negative stigma in society, so it needs to get used to dealing with this situation. Habituation or habituation is a process when someone or the people around us gradually in their daily lives do something that often happens repeatedly. Regarding the social religious habituation that is often encountered, it usually determines that individuals go through a process of having to get used to living together with the social norms surrounding the environment in which they live as well as those related to religion itself. The aim of this research is (1) to find out what the life of a Ladies Companion (LC) is like in Mojokerto City. (2) know how a Ladies Companion (LC) manages her social and religious matters at the same time as her work. This research uses a descriptive qualitative research method by analyzing the results obtained when involved in the field. Data collection techniques were carried out using observation, interviews and documentation. From the results of the research conducted, it can be concluded that the two subjects have social and religious habitus that are minimally carried out in their daily lives. Where they are too focused on what their life goals are. This research involves Bourdieu's theory which explains that habits exist because they enter a new atmosphere in which there is capital and a domain for their survival.